Proximal Femur Osteotomy Guided with Patient-Specific 3D Print Technology: A Case Report. Issue 3 (July 2021) - Valdovino, Alan; Ryan, Justin; Gholami, Parham; Bomar, James D.; Upasani, Vidyadhar V.
Abstract : Case: We present a 17-month-old female infant with a left lower extremity infection. After treating the infection, she developed a pathologic femur fracture malunion with a complex femoral deformity. Three-dimensional (3D) patient-specific prints of her affected and unaffected femora were made, and a corrective osteotomy was templated on the prints. Conclusion: By printing the contralateral proximal femur and templating the osteotomy and correction based on the native anatomy of the patient, we were able to simulate the 3D deformity correction and customize an implant to fit the patient's anatomy.